2013
DOI: 10.3758/s13415-013-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of automatic change detection shown by the visual mismatch negativity: An additional feature is identified faster than missing features

Abstract: In two experiments, we demonstrated that an asymmetric effect of brain electric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Full T3 deviants may have elicited greater MMNs because they have more complex contours than the other tones. It has been shown that the MMN is sensitive to the number of features in the standards and deviants: a deviant with an added feature (e.g., deviants consisting of combined white noise and sine tones after standards consisting of only white noise or only sine) elicits a larger MMN than the reverse case [3,12]. T3, which has a falling-rising contour when pronounced in isolation or phrasefinally, may also have been considered to have an additional phonetic feature by the listeners.…”
Section: Discussionmentioning
confidence: 99%
“…Full T3 deviants may have elicited greater MMNs because they have more complex contours than the other tones. It has been shown that the MMN is sensitive to the number of features in the standards and deviants: a deviant with an added feature (e.g., deviants consisting of combined white noise and sine tones after standards consisting of only white noise or only sine) elicits a larger MMN than the reverse case [3,12]. T3, which has a falling-rising contour when pronounced in isolation or phrasefinally, may also have been considered to have an additional phonetic feature by the listeners.…”
Section: Discussionmentioning
confidence: 99%
“…This means that hearing a deviant /f/ token in a stream of /s/ tokens could amount to detecting a decrease in energy or an absence of information, whereas hearing a deviant /s/ token in a stream of /f/ tokens would amount to detecting an increase of energy or an addition of information. 8 There is indeed ample evidence that a deviant which is missing an acoustic feature present in the standards elicits an attenuated MMN (or no MMN at all) compared to a deviant which has an additional acoustic feature not present in the standards (Nordby, Hammerborg, Roth, & Hugdahl, 1994 ; Sabri & Campbell, 2000 ; Timm, Weise, Grimm, & Schröger, 2011 ; see also Czigler, Sulykos, & Kecskés-Kovács, 2014 , for a corresponding effect in the visual counterpart of the MMN). While these studies all used non-linguistic stimuli, similar asymmetries based on feature salience have been seen for linguistic stimuli in behavioural studies (Nielsen, 2011 ; Nielsen & Scarborough, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an inherent problem of this procedure, the to-be-compared ERPs are selected from highly different sequences. Furthermore, in many cases it is difficult to vary properly the stimuli of the control sequence (e.g., in case of female vs. male photographs, [ 24 ]; feature absence vs. feature presence in vMMN studies, [ 25 ]). Our paradigm attempts to solve the low-level adaptation issue using the opposite logic.…”
Section: Introductionmentioning
confidence: 99%